2011
DOI: 10.1016/j.marpetgeo.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Geologic controls on gas hydrate occurrence in the Mount Elbert prospect, Alaska North Slope

Abstract: a b s t r a c tData acquired at the BPXA-DOE-USGS Mount Elbert Gas Hydrate Stratigraphic Test Well, drilled in the Milne Point area of the Alaska North Slope in February, 2007, indicates two zones of high gas hydrate saturation within the Eocene Sagavanirktok Formation. Gas hydrate is observed in two separate sand reservoirs (the D and C units), in the stratigraphically highest portions of those sands, and is not detected in non-sand lithologies. In the younger D unit, gas hydrate appears to fill much of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 29 publications
4
75
0
Order By: Relevance
“…The region is of particular interest because of the presence of numerous major gas and oil fields including the Prudhoe Bay, Milne Point, and Kuparuk River oil fields (Carman and Hardwick, 1983;Collett, 1993;Bird, 1999;Boswell et al, 2011). Large quantities of oil have been produced, since the discovery of the first field in 1968, from complex structural/stratigraphic traps within Permian to Cenozoic reservoirs at production depths >2000 m (>6562 ft) .…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The region is of particular interest because of the presence of numerous major gas and oil fields including the Prudhoe Bay, Milne Point, and Kuparuk River oil fields (Carman and Hardwick, 1983;Collett, 1993;Bird, 1999;Boswell et al, 2011). Large quantities of oil have been produced, since the discovery of the first field in 1968, from complex structural/stratigraphic traps within Permian to Cenozoic reservoirs at production depths >2000 m (>6562 ft) .…”
Section: Geological Settingmentioning
confidence: 99%
“…The principal structural features of the region ( Figure 1A) are the Barrow Arch to the north, and the Colville Basin and Brooks Range to the south (Carman and Hardwick, 1983;Bird, 1999;Boswell et al, 2011). The Barrow Arch is an eastwest-trending rift shoulder and the Brooks Range is a fold and thrust mountain belt related to continentcontinent collision (Bird, 1999).…”
Section: Geological Settingmentioning
confidence: 99%
“…The base of permafrost on the ANS ranges from 220 m to 660 mbgs (meters below ground surface) (Collett et al, 1988), but at the Mount Elbert well site ice-bearing permafrost currently extends to a depth of about 536.4 m RKB. Another hypothesis suggests that hydrate formation may have preceded the full development of permafrost (Collett et al, 2011b;Boswell et al, 2011;Dai et al, 2011).…”
Section: Geologic Setting and Gas Hydrate Presencementioning
confidence: 99%
“…Recent studies have concluded that methane hydrate (hereafter hydrate), a naturally occurring clathrate compound consisting of molecular water cages surrounding gas molecules (primarily methane), contains large quantities of methane in shallow sediments throughout the world's coastal margins and polar regions [Boswell et al, 2010;Milkov, 2004;Sloan et al, 1998]. Each cubic meter of hydrate can hold approximately 160 m 3 of natural gas at standard temperature and pressure [National Resource Council, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Known deposits of methane hydrate are present in regions beneath the north slope of the Brooks Range where conditions are suitable for methane hydrate occurrence. These hydrate-bearing strata are confined by low-permeability layers [Boswell et al, 2010], making depressurization the apparent method for production. …”
mentioning
confidence: 99%